Perspectives on the role of materials in sustainable product design education - Karen Marie Hasling (Temes de Disseny)
This paper discusses present and future roles of materials in sustainable design with a focus on design education. With a multifaceted understanding of materials, from an educational perspective, the challenge is to ensure that students are able to navigate within the materials in the design field and to reflect on its potentials and limitations in the process. Moreover, when further targeting materials within a design for sustainability agenda that is complex in itself, it has been observed that students find it overwhelming. Accordingly, the paper unfolds ways of understanding the role of materials in sustainable design education as a way to demonstrate the positions they can take as future designers.